The pillars of the earth - Follett, Ken.; Case, David (New York : Willian Morrow, 1989)
Set in the twelfth-century England when the empress Maud and Stephen are fighting for the crown of England after the death of Henry, chronicles the struggle to build a cathedral.
In 3 containers (24 cm.).
Unabridged version of the book read by David Case.
Keywords: Cathedrals -- Design and construction -- Fiction; Great Britain -- History -- Stephen, 1135-1154 -- Fiction